If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + 6x + -12 = -8 + -4x + 9x Reorder the terms: 18 + -12 + 6x = -8 + -4x + 9x Combine like terms: 18 + -12 = 6 6 + 6x = -8 + -4x + 9x Combine like terms: -4x + 9x = 5x 6 + 6x = -8 + 5x Solving 6 + 6x = -8 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6 + 6x + -5x = -8 + 5x + -5x Combine like terms: 6x + -5x = 1x 6 + 1x = -8 + 5x + -5x Combine like terms: 5x + -5x = 0 6 + 1x = -8 + 0 6 + 1x = -8 Add '-6' to each side of the equation. 6 + -6 + 1x = -8 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = -8 + -6 1x = -8 + -6 Combine like terms: -8 + -6 = -14 1x = -14 Divide each side by '1'. x = -14 Simplifying x = -14
| (9x^(1/2))^2 | | 14z-7/7 | | 2*B+3*A=5 | | (14x-27y)+(32x+65y)= | | 5/6x^2*3/6x^2 | | 3(x-4)=12x-4-9x | | 2x^3-15x^2+24x+12=0 | | (50x-8y)+(32x+37y)= | | 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 | | 35x+-14=36x+-6 | | -18=x+20 | | 36x-14=36x-6 | | -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= | | x-24=6 | | 2(2)+3(4a)-4(3+3a)+3=0 | | 3y-24-6y+37= | | 4d^2-4d-80=0 | | x-8.8=-6.8 | | 2=2m+2+6m | | (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x |